Identification of novel diagnostic biomarkers for deep venous thrombosis. (19th April 2018) - Memon, Ashfaque A.; Sundquist, Kristina; PirouziFard, Mirnabi; Elf, Johan L.; Strandberg, Karin; Svensson, Peter J.; Sundquist, Jan; Zöller, Bengt
Summary: The combination of a negative D‐dimer and a Wells score can rule out, but not confirm, a diagnosis of deep venous thrombosis (DVT). We aimed to identify new diagnostic biomarkers for DVT and to investigate their relationship with hypercoagulability markers [D‐dimer and activated protein C‐protein C inhibitor (APC‐PCI) complex]. We screened 92 cardiovascular‐specific proteins in plasma samples from 45 confirmed DVT patients and 45 age‐ and sex‐matched non‐DVT patients selected from a prospective multicentre diagnostic management study (SCORE) by Proseek Multiplex CVDIII 96×96 . Plasma levels of 30 proteins were significantly different between DVT and non‐DVT patients. After Bonferroni correction, plasma levels of seven proteins: P‐selectin, transferrin receptor protein 1, von Willebrand factor, tissue factor pathway inhibitor, osteopontin (OPN), bleomycin hydrolase and ST2 protein remained significantly different. The area under curve (AUC) for these proteins ranged from 0·70 to 0·84. Furthermore, all seven identified proteins were significantly associated with markers of hypercoagulability. A combination of OPN and APC‐PCI had the best ability to discriminate DVT from non‐DVT patients (AUC = 0·94; sensitivity = 89% and specificity = s84%). In conclusion, we identified multiple proteins associated with markers of hypercoagulability and with a potential to become novel diagnostic biomarkers for DVT.